2022
DOI: 10.1038/s41420-022-00813-z
|View full text |Cite
|
Sign up to set email alerts
|

KLF2 up-regulates IRF4/HDAC7 to protect neonatal rats from hypoxic-ischemic brain damage

Abstract: Neonatal brain hypoxic ischemic injury is a devastating event causing permanent brain damage. The current study set out to explore the role of Kruppel-like factor 2 (KLF2) and its downstream molecular mechanism on hypoxic-ischemic brain damage (HIBD) in neonatal rats. First, we adopted a modified Rice method to develop a HIBD model in postnatal day seven Sprague Dawley (SD) rat pups. Next, neuronal damage, morphological changes, and neuronal apoptosis were documented in the vulnerable hippocampal CA1 region an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Over-expression of PGC-1α in neurons could inhibit the neuronal apoptosis, while inhibition of PGC-1α expression could induce the neuronal apoptosis (Yang et al, 2022b). It was found that the expression of PGC-1α and related antioxidant components were increased in AIS patients, and the increased level of PGC-1α was mainly located in activated astrocytes (Wu and Li, 2022;Wu et al, 2015). By over-expressing PGC-1α in astrocytes in vitro, ROS levels were reduced, pro-in ammatory factor release was reduced, and neuronal activity was ultimately improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over-expression of PGC-1α in neurons could inhibit the neuronal apoptosis, while inhibition of PGC-1α expression could induce the neuronal apoptosis (Yang et al, 2022b). It was found that the expression of PGC-1α and related antioxidant components were increased in AIS patients, and the increased level of PGC-1α was mainly located in activated astrocytes (Wu and Li, 2022;Wu et al, 2015). By over-expressing PGC-1α in astrocytes in vitro, ROS levels were reduced, pro-in ammatory factor release was reduced, and neuronal activity was ultimately improved.…”
Section: Discussionmentioning
confidence: 99%
“…As is known to all, the research of miR-126a-5p focuses on the eld of cancer treatment (Wu and Li, 2022), and the research on AIS and neuronal injury is still a blank. In order to further study the molecular mechanism of miR-126a-5p in AIS and neuronal injury, we rst analyzed the potential target circRNA binding by miR-126a-5p.…”
Section: Mir-126a-5p Is the Target Gene Of Circrna_0000927mentioning
confidence: 99%
“…Second, the pathogenesis of neonatal HIE is complicated; we only focused on oxidative stress and apoptosis, and other pathological factors, such as inflammation, mitochondrial dysfunction and Frontiers in Pharmacology frontiersin.org excitotoxicity, might be involved. Finally, the expression of Nrf2 can be enhanced by the activation of silent information regulator 2-related enzyme 1 (SIRT1), ameliorating HIBD-induced ferroptosis and exerting a neuroprotective effect (Li C. et al, 2022). Whether EA can alleviate HIBD by inhibiting ferroptosis through the SIRT1/ Nrf2 signaling pathway needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we also found obvious cerebral infarct areas in the HI group, which were then decreased by EA administration. Morphological changes in the ipsilateral brain are one of the major characteristics of neonatal HIE ( Wu and Li, 2022 ). In the present study, we observed morphological injuries in the ipsilateral parietal cortex and the hippocampal CA1 region by H&E staining, and the results showed that EA treatment attenuated HIBD-mediated neuronal atrophy and their disordered distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Aging Neuroscience 09 frontiersin.org (Wu and Li, 2022). Hdac7 was down-regulated in postoperative period.…”
Section: Functional Enrichment Analysis and Subclassificationmentioning
confidence: 93%